O papel do sistema dopaminérgico nigroestriatal na neurobiologia do sono - Lima, Marcelo de Meira Santos [UNIFESP] (2008)
Dopamine (DA) is critically involved in regulating neural processes responsible for complex movements and emotions. Alterations in central dopaminergic neurotransmission have been implicated in important neurological and psychiatric disorders such as Parkinson’s disease (PD) and schizophrenia. In addition, DA has recently been recognized as instrumental in the regulation of sleep-wake states. Herein, we present evidence that tyrosine hydroxylase (TH) is down-regulated in the nigrostriatal pathway after 24 h of sleep deprivation (SD) in mice. To identify the involvement of DA in SD and sleep rebound (R) we administered reserpine (1 mg/kg) associated to a-methyl-p-tyrosine (aMT) (250 mg/kg) to produce DA depletion, and rotenone (10 mg/kg) to increase striatal DA turnover. Behavioral tests (catalepsy, grasping and open-field) were conducted to evaluate muscular rigidity and motor alterations inflicted by the drugs immediately after SD and R. Western blot and immunohistochemistry demonstrated that SD alone produced important down-regulation on TH protein expression within the substantia nigra (SN), without affecting the number of dopaminergic neurons. Pharmacological depletion of DA or increase of its turnover affected the entire nigrostriatal pathway. We propose that downregulation of TH expression produced by SD greatly explains the existence of supersensitivity of dopaminergic D2 receptors, especially along the nigrostriatal pathway, and suggest a novel role of DA in the mediation of sleep-wake states as a consequence of the modulation of TH protein expression along that pathway. The implications of these alterations may directly reverberate in motor and sleep abnormalities found in patients with PD.